DESGW Optical Follow-up of BBH LIGO-Virgo Events with DECam. Issue Volume 13:Issue S338(2017) (29th January 2019) - Butler, Robert E.; Soares-Santos, M.; Annis, J.; Herner, K.; ,
Abstract: The DESGW program is a collaboration between members of the Dark Energy Survey, the wider astronomical community, and the LIGO-Virgo Collaboration to search for optical counterparts of gravitational wave events, such as those expected from binary neutron star mergers or neutron star-black hole mergers. While binary black hole (BBH) events are not expected to produce an electromagnetic (EM) signature, emission is certainly not impossible. The DESGW program has performed follow-up observations of four BBH events detected by LIGO in order to search for any possible EM counterpart. Failure to find such counterparts is still relevant in that it produces limits on optical emission from such events. This is a review of follow-up results from O1 BBH events and a discussion of the status of ongoing uniform re-analysis of all BBH events that DESGW has followed up to date.